Neutronic analysis of a heat-pipe cooled reactor - Josef Sabol; Jan Frýbort (Acta Polytechnica CTU Proceedings, 2023)
Heat-pipe cooled reactors belong to the group of nuclear reactors using heat pipes filled with liquid metals (such as sodium or potassium) to cool the core. Due to the passive heat removal system, there is no need to use closed loops with pumps, and the reactor can be operated with reduced operational requirements. Consequently, this system can be used in remote locations without access to an electrical grid, or it can be used for space applications. This paper deals with a neutronic study of the Special Purpose Reactor Design-B concept from the Idaho National Laboratory. Using Monte Carlo code Serpent 2 and ENDF/B VIII.0 library, a fixed-temperature model was created to calculate the safety characteristics of the system. This included reactivity coefficients, power distribution, neutron flux spectrum, and criticality safety. In a simplified depletion calculation, an effect of fuel depletion on safety systems was determined as well as a decay heat.